1990
DOI: 10.1002/j.1460-2075.1990.tb07515.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the substrate binding sites of human galactosyltransferase by protein engineering.

Abstract: An expression vector, pIN‐GT, encoding the soluble form of beta 1,4‐galactosyltransferase (GT) has been constructed from human GT cDNAs and the pIN‐III‐ompA2 expression vector. Escherichia coli strain SB221 harboring the pIN‐GT plasmid produces and secretes a fusion protein consisting of the ompA signal and GT. The expression of GT was detected by assaying enzymatic activity as well as by Western blotting using anti‐GT antibodies. The recombinant GT was purified to homogeneity by N‐acetylglucosamine‐Sepharose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…If the Mnt1/Gal-Tf fusions had inserted into yeast organelle membranes as the authentic Mnt1 and Gal-Tf proteins (4,11,34), which are type II membrane proteins, it could be expected that they are refractory to the action of proteases. To test this notion crude extracts of phMGT1 and phMGT3 transformants were treated with proteinase K in the presence and absence of Triton X-100; subsequent to the treatments the Gal-Tf fusion protein was analyzed on immunoblots using the anti-Gal-Tf antibody.…”
Section: Construction Of Mnt1::gal-tf Genementioning
confidence: 99%
See 1 more Smart Citation
“…If the Mnt1/Gal-Tf fusions had inserted into yeast organelle membranes as the authentic Mnt1 and Gal-Tf proteins (4,11,34), which are type II membrane proteins, it could be expected that they are refractory to the action of proteases. To test this notion crude extracts of phMGT1 and phMGT3 transformants were treated with proteinase K in the presence and absence of Triton X-100; subsequent to the treatments the Gal-Tf fusion protein was analyzed on immunoblots using the anti-Gal-Tf antibody.…”
Section: Construction Of Mnt1::gal-tf Genementioning
confidence: 99%
“…The complex type of N-glycosyl chains in mammalian cells is synthesized after trimming of the core unit by the sequential addition of GlcNAc, Gal, and NeuAc. Galactose addition in human cells is mediated by UDP-galactose: Nacetyl-D-glucosaminyl-glycopeptide 4␤-D-galactosyltransferase (EC 2.4.1.38) (Gal-Tf), 1 an enzyme anchored in the Golgi membrane, which uses UDP-Gal as substrate and GlcNAc on glycosyl structures as acceptors (3,4). In its secreted soluble form, which lacks a membrane anchor region, Gal-Tf functions as lactose synthase, while a third role of Gal-Tf, correlated with its localization on the cell surface, is to mediate adhesion processes (5).…”
mentioning
confidence: 99%
“…Thus kinetic studies of mutagenized soluble hGal-T, expressed in different systems, have been extensively used to identify amino acids important for its catalytic activity. Thus it has been shown that Tyr284, Tyr309 and Trp310 are critically involved in GlcNAc binding and Tyr309 involved in UDP-Gal binding (Aoki et al, 1990). Also, based on kinetic studies on mutagenized enzyme forms, it has been proposed that Cys129 and Cys245 are implicated in a disulfide bond which holds the Gal-T in a conformation that is required for its catalytic activity and Cys340 may be involved in the binding of UDP-Gal (Wang et al, 1994).…”
mentioning
confidence: 99%
“…The availability of galactosyltransferase cDNA opens the way to the investigation of the structure-function relationships of galactosyltransferase by recombinant techniques. The functional domains of mammalian galactosyltransferase have been studied by various laboratories by expressing cDNA clones in both bacterial and mammalian cells (Masibay and Qasba, 1989;Aoki et al, 1990;Nakazana et al, 1993). Based on amino acid sequence similarities and conserved structural features, eucaryotic and bacterial galactosyltransferases can be classified into five families; A, B, C, D and E (Breton et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Region II contains an acidic motif, EDD, surrounded by two stretches of hydrophobic residues, which exhibits hydrophobic cluster analysis (Gaboriaud et al, 1987) similarity with the DVD and DXD motifs of families A and B, respectively (Breton et al, 1998). This is located in a region of the catalytic domain that has been implicated in UDPgalactose binding by chemical Brew, 1990, 1991) and mutational studies (Aoki et al, 1990;Zu et al, 1995) The structural and functional relationships of mammalian galactosyltransferase have been well studied, but bacterial galactosyltransferase is poorly understood. Recently, we cloned and expressed β-1,4-galactosyltransferase from Neisseria meningitidis and Neisseria gonorrhoeae (Park et al, 2002).…”
Section: Introductionmentioning
confidence: 99%